OS ATOS PROCESSUAIS DEFEITUOSOS E A CRISE DA TEORIA DAS NULIDADES: A FORMA COMO GARANTIA. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
Defective procedural acts and the crisis in the theory of nullity is a necessary study to better understand the mechanisms for protecting the fundamental guarantees of the accused in criminal proceedings. The Brazilian Justice System has the duty to respect the forms that constitute the procedural acts, under penalty of being declared null in favor of the defense of the inherent rights of the defendants. Through the literature review methodology, this article aims to make a quick conceptualization about the theory of nullities and then turn the discussion in the face of the traditional thesis and widely applied in our Brazilian legal system, which in turn seeks to classify the atypicalities procedural as sanctions, and conceptualize nullities as absolute or relative, to then analyze whether the current system of procedural invalidity, in force in the Brazilian legal system, uses premises consistent with the adopted principle system, in addition to analyzing whether such premises really depart from the constitutional matrix, structuring itself from the concept of defective procedural act.